SISTIM BUDIDAYA LORONG (ALLEY CROPPING) PADA PERTANAMAN KAKAO DENGAN TANAMAN NILAM DI KECAMATAN MALANGKE KABUPATEN LUWU UTARA - Sapareng, Sukriming (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2017)
Its objective is to provide knowledge and skills to the group of partners to increase the capability cultivation technology systems patchouli Alley Cropping on the sidelines of cocoa cropping, and produce quality patchouli oil products from the harvest and post-harvest handling is optimal. Alley Cropping system as part of efforts to increase the income of cocoa farmers through the use of empty space in between cocoa cropping. The method used is the counseling and training with material knowledge of basic techniques Alley Cropping systems and knowledge in harvesting and postharvest handling of patchouli. In addition, it is expected an increase in the cultivation of partner skills Alley Cropping system patchouli on the sidelines of cocoa cropping. Of the activities carried out can be concluded that the concept of Alley Cropping received enough good of the citizens to be applied on cocoa plantations. Knowledge of patchouli cultivation techniques applied include the selection of superior varieties, breeding, maintenance techniques, reduction and prevention of pests and diseases, cover and lighting requirements for patchouli, and staple crops and plant maintenance stream.